The Shifts of Diazotrophic Communities in Spring and Summer Associated with Coral Galaxea astreata, Pavona decussata, and Porites lutea - Zhang, Yanying; Yang, Qingsong; Ling, Juan; Van Nostrand, Joy D.; Shi, Zhou; Zhou, Jizhong; Dong, Junde (Frontiers in Microbiology, 2016)
The coral holobiont often resides in oligotrophic waters; both coral cells and their symbiotic dinoflagellates possess ammonium assimilation enzymes and potentially benefit from the nitrogen fixation of coral-associated diazotrophs. However, the seasonal dynamics of coral-associated diazotrophs are not well characterized. Here, the seasonal variations of diazotrophic communities associated with three corals, Galaxea astreata, Pavona decussata and Porites lutea, were studied using nifH gene amplicon pyrosequencing techniques. Our results revealed a great diversity of coral-associated diazotrophs. nifH sequences related to Alphaproteobacteria, Deltaproteobacteria and Gammaproteobacteria were ubiquitous and dominant in all corals in two seasons. In contrast with the coral P. decussata, both G. astreata and P. lutea showed significant seasonal changes in the diazotrophic communities and nifH gene abundance. Variable diazotroph groups accounted for a range from 11% to 49% within individual coral samples. Most of the variable diazotrophic groups from P. decussata were species-specific, however, the majority of overlapping variable groups in G. astreata and P. lutea showed the same seasonal variation characteristics. Rhodopseudomonas palustris- and Gluconacetobacter diazotrophicus-affiliated sequences were relatively abundant in the summer, whereas a nifH sequence related to Halorhodospira halophila was relatively abundant in spring G. astreata and P. lutea. The seasonal variations of all diazotrophic communities were significantly correlated with the seasonal shifts of ammonium and nitrate, suggesting that diazotrophs play an important role in the nitrogen cycle of the coral holobiont.